Analysing the peer relationships of obese and normal-weight preschool children aged between five and six years - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
The objective of this study is to reveal whether the peer relationships of preschool children who are determined to be obese, based on their body mass index (BMI), differentiate or not. The study was conducted within the frame of a relational survey model. A total of 114 five- to six-year-old children (57 normal-weight children and 57 obese children), who attend preschool educational institutions, participated in the study. The Ladd-Profilet Child Behaviour Scale and Peer Victimisation Scale were used to obtain data of the study. Multivariate Analysis of Variance (MANOVA) was used to test the data. As a result of the study, there were significant differences on prosocial behaviour and hyperactivity levels of children according to their gender and at aggressiveness, prosocial behaviour and hyperactivity levels according to the state of being obese. Besides, significant differences were observed on asocial behaviours, hyperactivity and peer victimisation levels of children according to the state of being obese and gender interaction.
Keywords: five- to six-year-old children; obesity; obese children; peer relationships; peer victimisation; ATTENTION-DEFICIT/HYPERACTIVITY DISORDER; OVERWEIGHT; CHILDHOOD; VICTIMIZATION; PERCEPTIONS; ATTITUDES; ADHD; FAT